2017
DOI: 10.1097/sap.0000000000001144
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Cervical Artery Perforator Flap

Abstract: The main purpose of head and neck reconstructive surgery is to provide anatomic restoration of the demolited region and to provide preservation and recovery of function. The anatomical investigations conducted over the years has enabled a detailed knowledge of human body vascularization, giving the opportunity to design and harvest more and more versatile and refined flaps, with increasingly satisfactory results. Even if in the last 2 decades free flaps have been considered a reconstructive criterion standard,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that the length of the superficial cervical artery could reach approximately 5 cm. 1,20 The pedicle length from the takeoff of the superficial cervical artery was 7.3 ± 2.0 cm (4.7-9.7 cm) in our cadaver dissections. This was the maximal vessel length when the perforator flap was elevated.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Previous studies have shown that the length of the superficial cervical artery could reach approximately 5 cm. 1,20 The pedicle length from the takeoff of the superficial cervical artery was 7.3 ± 2.0 cm (4.7-9.7 cm) in our cadaver dissections. This was the maximal vessel length when the perforator flap was elevated.…”
Section: Discussionmentioning
confidence: 79%
“…Because the definition of a perforator flap with a muscle cuff remains controversial and conceptually overlaps with the myocutaneous flap or muscle pedicled flap, 10 articles reporting perforator flaps with a muscular cuff were discarded 2,3,6,13–19 . One study of transverse cervical artery perforator flaps was discarded because some flaps might be pedicled by the supraclavicular perforator 20 . Finally, 6 articles were considered for use in this review 21–26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, the use of the transverse cervical artery and internal jugular vein as recipient vessels for the ALT free flap enabled us to address above-mentioned difficulties that are reluctant to perform a free flap in this region. Because the transverse cervical artery has sufficient length and originates from the subclavian artery (56.7%) or the thyroid-cervical trunk (42.4%) and continues to the scapular area as the descending branch of the transverse cervical artery (also called the dorsal scapular artery), this artery can provide a reliable recipient artery for the microvascular free flap reconstruction of posterior cervicothoracic defects [4,8]. However, the lack of a recipient vein around defect areas remains a reluctance to perform a free flap for many surgeons.…”
Section: Discussionmentioning
confidence: 99%